The Theme of Love in Religious Education Built on the Story of Psyche and Orual - Lucia Bieliková (Theology and Philosophy of Education)
The article presents a brief analysis of the well–known novel by C. S. Lewis Till We Have Faces with regard to its didactic potential in religious or ethical education. It focuses on the theme of love and the fundamental principles on which interpersonal relationships should be built from a Christian perspective. In the story of the mythological sisters Orual and Psyche, the author has depicted all the key ideas about the nature of love and its relationship to God that are also found in Deus caritas est, the encyclical on the love of God by Benedict XVI. The ambition of this article is to present these basic motivational story lines as a starting point for the possible use of this work in school teaching or catechesis.